2019
DOI: 10.1155/2019/4530534
|View full text |Cite|
|
Sign up to set email alerts
|

miR-221 Alleviates the Ox-LDL-Induced Macrophage Inflammatory Response via the Inhibition of DNMT3b-Mediated NCoR Promoter Methylation

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease, and macrophages play a key role in all phases of AS. Recent studies have shown that miR-221 is a biomarker for AS and stroke; however, the role and mechanism of miR-221 in AS are unclear. Herein, we found that miR-221 and NCoR levels were decreased in ox-LDL-treated THP-1-derived macrophages. In contrast, DNMT3b, IL-6, and TNF-α expression levels were increased under these conditions. Upregulation of miR-221 or NCoR could partially inhibit ox-LDL-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
(42 reference statements)
3
6
0
Order By: Relevance
“…1 B). These results suggest that DNMT3B limits alternative macrophage polarization, corroborating previous reports [ 17 , 32 ]. Next to alternative macrophages, classically activated macrophages are present in the lungs of IPF patients [ 33 ].…”
Section: Resultssupporting
confidence: 92%
“…1 B). These results suggest that DNMT3B limits alternative macrophage polarization, corroborating previous reports [ 17 , 32 ]. Next to alternative macrophages, classically activated macrophages are present in the lungs of IPF patients [ 33 ].…”
Section: Resultssupporting
confidence: 92%
“…23 As reported, DNMT3B inhibition remarkably inhibited ox-LDL-induced macrophage inflammatory. 36 In the current study, we found that DNMT3B expression was significantly elevated in AS patient tissues. Consistently, DNMT3B negatively regulated PTPN2 expression in ox-LDL-treated HUVECs.…”
Section: Discussionsupporting
confidence: 52%
“…On the one hand, ox-LDL activates numerous inflammatory factors and promotes inflammatory cell infiltration. On the other hand, activated macrophage cytophagy and degraded ox-LDL lead to the accumulation of cholesterol and formation of foam cells [26,27]. These data suggest that TNF-α and IL-6 were enhanced during foam cell formation, but this effect was reversed synergistically by MP and LOX-1 gene silencing, indicating that LOX-1 inhibition and MP intervention could synergistically and markedly suppress foam cell formation.…”
Section: Discussionmentioning
confidence: 99%